2021
DOI: 10.1371/journal.pone.0250549
|View full text |Cite
|
Sign up to set email alerts
|

How far from the gold standard? Comparing the accuracy of a Local Position Measurement (LPM) system and a 15 Hz GPS to a laser for measuring acceleration and running speed during team sports

Abstract: Purpose This study compared the validity and inter- and intra-unit reliability of local (LPM) and global (GPS) position measurement systems for measuring acceleration during team sports. Methods Devices were attached to a remote-controlled car and validated against a laser. Mean percentage biases (MPBs) of maximal acceleration (amax) and maximal running speed (vmax) were used to measure validity. Mean between-device and mean within-device standard deviations of the percentage biases (bd-SDs and wd-SDs) of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…For example, when comparing V max measurements provided by an LG and 5 Hz GPS devices, Nagahara et al (53), detected a systematic error bias of 4.8% (higher V max values in favor of LG measurements; confidence limits [26.3 to 3.3] and a TE of 5.1 m$s 21 ). In summary, GPS devices underestimated V max compared with the LG (mean values of V max equal to 8.12 and 8.54 m$s 21 , respectively) (53). It is worth noting that, even with the recent evolution in GPS technologies, the slight increase in sampling frequency (from 1 to 5 Hz) does not represent a consistent improvement in data collection, especially for those measurements occurring at high movement velocities (i.e., V max ).…”
Section: Validity Reliability and Sensitivity For V Max Measures With...mentioning
confidence: 87%
See 1 more Smart Citation
“…For example, when comparing V max measurements provided by an LG and 5 Hz GPS devices, Nagahara et al (53), detected a systematic error bias of 4.8% (higher V max values in favor of LG measurements; confidence limits [26.3 to 3.3] and a TE of 5.1 m$s 21 ). In summary, GPS devices underestimated V max compared with the LG (mean values of V max equal to 8.12 and 8.54 m$s 21 , respectively) (53). It is worth noting that, even with the recent evolution in GPS technologies, the slight increase in sampling frequency (from 1 to 5 Hz) does not represent a consistent improvement in data collection, especially for those measurements occurring at high movement velocities (i.e., V max ).…”
Section: Validity Reliability and Sensitivity For V Max Measures With...mentioning
confidence: 87%
“…Notwithstanding, different limitations should be considered when interpreting the findings of these studies (15,25,42,43,53): (a) the use of TG values as criterion measures; (b) testing under more controlled (i.e., less complex) conditions, which may indirectly increase validity and reliability of assessments (i.e., linear sprinting, smoothing of data points, static starts, no changes of direction); and (c) lack of sensitivity of measurements reported in the majority of studies. Finally, it should be noted that the accuracy strongly depends on the task being measured (21), with nonlinear sprints (e.g., maximal sprints with directional changes), for example, showing poorer validity, which compromises the use of GPS-derived V max for analyzing and quantifying sprint performance in team sports.…”
Section: Massard Et Al (mentioning
confidence: 99%
“…Finally, we chose the mean absolute acceleration/ deceleration as a metric for the acceleration load. Although the measurement of accelerations and decelerations within specific ranges may provide more detailed information regarding this load, limited validity regarding the measurement of instantaneous accelerations with the GNSS has repeatedly been reported (1,5,12), especially around changes of direction (12), which are common during SSGs.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors demonstrated that the accuracy of these instruments varies depending on the specific type of action being measured. This inaccuracy can lead to an underestimation of the workloads during trainings and matches [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%